Skrining Fitokimia Daun Binahong (Anredera cordifolia) - Oileri Tikirik, Wita; Almafira, Mustika; Muchtar, Mursyid; Aminuddin, Aminuddin (Politeknik Negeri Ketapang, 2025)
Plants are a source of both chemical compounds the result of primary metabolism such as carbohydrates, protein, the fat that plants use for their growth, Nor as a source of secondary metabolic compounds such as alkaloids, flavonoid, steroids/terpenoid, saponin and tannin. One of the plants that have the potential to become traditional medicine is binahong.Parts of plants which are most often used as a medicine is a foliar part.Leaves binahong active compounds containing the alkaloid, flavonoid, saponin and tannin.The use of traditional spread in various areas, both in urban and rural area. One of the areas using traditional medicine is kecamatan papalang, mamuju district.This study was conducted to obtain the secondary to extract metabolir compound leaves binahong (Anredera cordifolia) growing in Papalang Mamuju District, by using the method screening phytochemistry.Extract leaves binahong obtained through maceration use a solvent ethanol 70% and was testing on these secondary by taking into account the color change after a reagent color. Results showing that extracts leaves binahong (Anredera Cordifolia) 70% ethanol use solvents containing flavonoid, an alkaloid, tannin, steroids and terpenoid but not containing saponin. This study is expected to provide information related to the active compounds in the leaves of binahong, so it can support its use as a basic traditional medicines.